Analysis of the Effectiveness of Environmental Waste Management in Dawi Dawi Village - Ningsih, Wirdha; Susanti, Yayu (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study examines the effectiveness of waste management at the Dawi-Dawi Village Landfill in Pomalaa District, Southeast Sulawesi, focusing on the challenges and potential improvements in the current system. Waste management in Indonesia faces significant issues, including rapid population growth, urbanization, and ineffective waste disposal methods, particularly open dumping. The Dawi-Dawi Village Landfill, serving a population of 9,816, faces challenges such as insufficient modern technology, poor waste sorting, and low community participation. The study utilized a qualitative descriptive approach with a case study design, collecting data through observations, interviews, and surveys from local residents, waste management workers, and community leaders. The findings indicate that waste management is ineffective, with key issues in officer knowledge, waste sorting, and poor community engagement. Inadequate funding and outdated infrastructure further exacerbate these problems. However, the role of waste collectors in sorting recyclables and the local government’s recognition of infrastructure improvements offer some support. Recommendations include increasing waste collection frequency, implementing source-based sorting, establishing composting and recycling facilities, and transitioning to a sanitary landfill system. Additionally, training for landfill workers and stronger community involvement in waste management programs are crucial for enhancing sustainability. This research highlights the need for comprehensive improvements to waste management practices in Dawi-Dawi Village to achieve more effective and environmentally friendly solutions.